The Challenges of Online Learning During the Covid-19 Pandemic - Yustinus Budi Hermanto; Veronika Agustini Srimulyani (Jurnal Pendidikan dan Pengajaran, 2021)
The Covid-19 pandemic requires almost all human activity to shift to digital media, including education services. Now, education services must adapt to online learning methods. This change is a challenge for Indonesian education, which must also prepare students to adapt to face the challenges of the era of Society 5.0. This study aims to obtain information about online learning from home during the Covid-19 pandemic at the junior, senior, vocational, and university levels in Indonesia. Researchers also analyzed the differences in the mastery of learning technology in students and educators. This study used a questionnaire distributed via Google forms to students and educators using Facebook, e-mail, and WhatsApp Group (WAG). The total sample in this study was 108 educators and 386 students. From the independent sample t-test test, the following results were obtained: the mastery ability of MS office software and online learning technology in students was higher than students with significant differences; there was no significant difference between teacher and lecturer perceptions regarding the role of learning technology in the classroom and on the educational process of students. The success of online learning was highly dependent on several integrated components, such as students, educators, learning resources, and the technology used. The researcher also found several disadvantages of online learning, such as student discipline, lack of internet access, and lack of social interaction, common challenges for educational organizations and stakeholders.